Atom-Economic, Metal- and Halogen-Free Synthesis of Podands: α,ω-Diphosphines and Their Chalcogenides Separated by Alkane Diol Spacers - Oparina, Ludmila A.; Gusarova, Nina K.; Vysotskaya, Oksana V.; Kolyvanov, Nikita A.; Artem’ev, Alexander V.; Trofimov, Boris A. (Synthesis, 2012)
Secondary phosphines and phosphine chalcogenides add to the divinyl ether of α,ω-alkane diols regio- and chemoselectively under free-radical conditions (UV irradiation or AIBN, 2:1 reactants molar ratio) to give anti-Markovnikov diadducts in good to excellent yields (65–98%).
Keywords: addition; alkenes; ethers; phosphorylation; radical reactions